Deaths in Police Custody: The ‘acceptable’ consequences of a ‘law and order’ society? - Pemberton, Simon (Outlines. Critical Practice Studies, 2005)
This article seeks to explain the acceptance of the rising numbers of police custody deaths in England and Wales over the last 20 years. It argues that these deaths are a consequence of the transformation in the U.K., from a social democratic to an increasingly neo-liberal mode of social organisation. The article links the characteristics of the authoritarian state, which emerged at this point in time, to the current profile of police custody deaths. Then, by using interview material with those who have investigated these cases, the article seeks to understand the narratives which are mobilised to legitimate these deaths as the ‘acceptable’ consequences of a ‘law and order’ society.